Connectivity networks and delineation of disconnected coastal provinces along the Indian coastline using large‐scale Lagrangian transport simulations. Issue 6 (9th May 2022) - Bharti, D. K.; Guizien, Katell; Aswathi‐Das, M. T.; Vinayachandran, P. N.; Shanker, Kartik
Abstract: Ocean circulation is the engine of dispersal and population connectivity in marine ecosystems, knowledge of which is essential for conservation planning. Understanding connectivity patterns at a large scale can help define the spatial extent of metapopulations. In this study, we built connectivity networks from Lagrangian transport simulations of neutrally buoyant particles released along the Indian coastline, a significant region in the Indian Ocean. We assessed the variation in connectivity networks across release periods for the major drivers of oceanography including the two monsoonal seasons, El Niño–Southern Oscillation (ENSO) years and for the entire range of region‐specific pelagic larval durations (PLDs) for marine invertebrates. We detected well‐connected communities, mapped frequent connectivity breaks, and assessed the functional role of coastal areas within the connectivity network using node metrics. Network characteristics did not differ based on the ENSO year, but varied with season and PLD. Connectance for the Indian coastline was relatively low, ranging from 0.5% to 3.4%, and increased significantly for PLD larger than 20 d. The number of cohesive coastal communities decreased gradually from 60 (PLD < 4 d) to 30 (PLD > 20 d) with increasing PLD. Despite variation in the location of connectivity breaks with the time of particle release within a monsoonal season, four disconnected provinces were consistently identified across the entire PLD range, which partially overlapped with observed genetic and biogeographic breaks reported along the Indian coastline. Our results support the adoption of a coordinated management framework within each of the four provinces delineated in the present study.